Information System Data Processing Population Article 03 Village Residents Cibeber - Herlambang Putra Perdana; Nurti Rangga Wibawa Putra; Rina Kurniawati; Muthmainnah Muthmainnah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Effectiveness and efficiency are mandatory requirements in this modern era, not least in terms of population data processing at the RT/RW level. This is what underlies the authors carry out research related to the design of information systems for data processing residents of RW 03 Kel. Cyber. The problem that occurs is that data processing is still conventional where all archives are still recorded manually in the master book so that the data collection process takes a long time. And submitting a cover letter takes a long time because it has to match the existing data. In addition, data is often lost when transferring management from each period. Therefore, it is necessary to update by utilizing currently available technology to facilitate and simplify the work of the employees on duty. The solution proposed by the author to solve this problem is to use the waterfall method by creating a desktop-based application. The result to be achieved is to make it easier to store data using a database and the process of submitting correspondence becomes more effective and efficient.